77.4k views
8 votes
F(n) = 4n +3
g(n) = 3n²+2
Find f(n) - g(n)
help lol

User Nsivakr
by
5.6k points

2 Answers

6 votes

Answer:


f(n) - g(n) = (4n + 3) - (3 {n}^(2) + 2) \\ = 4n + 3 - 3 {n}^(2) - 2 \\ = \boxed{4n - 3 {n}^(2) + 1}

(4n²-3n+1) is the right answer.

User Markus Schnell
by
5.3k points
8 votes

Answer:


(4n + 3) - (3 {n}^(2) + 2) \\ = 4n + 3 - 3 {n}^(2) - 2 \\ = - 3 {n }^(2) + 4n + 1 \\ ( - 3 {n}^(2) - 3n) - (1n + 1) \\ - 3n(n + 1) - 1(n + 1) \\ (n + 1)( - 3n - 1) \\ n = - 1 \\ n= (1)/( - 3)

User Louis Shraga
by
3.9k points